Socially Responsive Human-Centred Framework for Data-Driven Educational Technologies: Implications for Digital Transformation in Indonesian Vocational Higher Education - Verawati Doloksaribu; Rabiatul Adawiyah Hasibuan; Heri Gunawan; Delima Simatupang; Dwi Suci Amaniarsih (Yayasan Sinergi Multidimensi Kreatif, 2026)
The rapid adoption of data-driven educational technologies (DDETs), including learning analytics, artificial intelligence (AI), and adaptive learning systems, has transformed higher education worldwide. However, their implementation continues to face persistent challenges related to digital equity, usability, algorithmic transparency, and ethical data governance, particularly in developing countries such as Indonesia. This study aims to develop a Socially Responsive Human-Centred Educational Technology (SR-HCET) framework by integrating the principles of ICT for Society (ICT4S) and Human-Centred Computing (HCC) to support inclusive digital transformation in Indonesian vocational higher education. A Systematic Literature Review (SLR) following the PRISMA 2020 guidelines was conducted using publications indexed in Scopus, Web of Science, and ERIC between 2015 and 2025. A total of 67 eligible studies were analysed through thematic synthesis to identify recurring social, technological, and governance challenges. The findings revealed four major issues: digital access inequality, algorithmic bias, ethical concerns in educational data governance, and usability limitations. The proposed SR-HCET framework integrates equity-by-design, human-centred usability, and ethical data governance as interdependent dimensions for designing responsible educational technologies. The study further discusses the implications of implementing this framework within Indonesian vocational higher education, where disparities in digital infrastructure, AI readiness, and institutional capacity remain significant. The proposed framework provides practical guidance for policymakers, institutional leaders, and educational technology developers in promoting equitable, transparent, and sustainable digital transformation.